Unmet clinical needs in women with polycystic ovary syndrome in regard to mental health: a cross-sectional study - Sourouni, Marina; Estermann, Julia; Bitterlich, Norman; Weidlinger, Susanna; Bachmann, Annette; Stute, Petra (Archives of gynecology and obstetrics, 2024)
Purpose: Polycystic ovary syndrome (PCOS) management has hardly been standardized until recent years. Despite the existence of a detailed, evidence-based guideline published by the European Society of Human Reproduction and Embryology (ESHRE), it remains unclear to what extent healthcare providers adhere to this guideline. Our aim is to evaluate the gynaecological medical care provided in women with PCOS, particularly in terms of mental health, from the patients’ perspective. Methods: For this cross-sectional online cohort study in women with PCOS, we designed a standardized, non-validated questionnaire covering aesthetic aspects, metabolism, menstrual cycle, reproduction, mental health, and prevention of chronic non-communicable diseases. Results: Among 1879 participants, various mental health aspects were reported: body image (n = 1879), eating patterns/habits (n = 1878), and emotional well-being (n = 1874). Although nearly all women (99.7%) reported complaints on at least one session of mental health, consultation rates were low (body image 9.7%, eating patterns/habits 16.6%, emotional well-being 4.4%). Mean satisfaction with counselling on the different domains varied from moderate to fairly satisfying, with scores of 56.0 points (SD 31.7), 53.5 points (SD 32.0), and 63.7 points (SD 30.2), respectively. More complaints were associated with lower satisfaction. The overall satisfaction with the management provided by the healthcare practitioner (HCP) was low, averaging 36.5 points (SD 29.7). Consequently, most women wished for more counselling (58.9%). Conclusion: Women affected by PCOS are not properly managed according to ESHRE guideline in regard to mental health issues. Overall consultation rates and corresponding satisfaction with management were poor, highlighting the need for significant improvements in healthcare provision.
Gesehen am 25.07.2024